2004
DOI: 10.1038/sj.bjp.0705870
|View full text |Cite
|
Sign up to set email alerts
|

Junctional and nonjunctional effects of heptanol and glycyrrhetinic acid derivates in rat mesenteric small arteries

Abstract: Heptanol, 18α‐glycyrrhetinic acid (18αGA) and 18β‐glycyrrhetinic acid (18βGA) are known blockers of gap junctions, and are often used in vascular studies. However, actions unrelated to gap junction block have been repeatedly suggested in the literature for these compounds. We report here the findings from a comprehensive study of these compounds in the arterial wall. Rat isolated mesenteric small arteries were studied with respect to isometric tension (myography), [Ca2+]i (Ca2+‐sensitive dyes), membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 51 publications
5
75
2
Order By: Relevance
“…It should be noted that although 18βGA has been widely used as gap junction inhibitor,27 this compound, as many of the gap junction blockers, may have non‐specific effects28 and clearly, future work should include more robust testing of their role, also by including membrane potential recordings.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although 18βGA has been widely used as gap junction inhibitor,27 this compound, as many of the gap junction blockers, may have non‐specific effects28 and clearly, future work should include more robust testing of their role, also by including membrane potential recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have been conducted previously on the contribution of cell-to-cell coupling to agonist-induced contractions in a variety of smooth muscle organs (Christ, 1995;Christ et al, 1996;Matchkov et al, 2004), in rat vas deferens the dynamics of recruitment of cells via different pathways, e.g. the Representative traces of the effect of 2 μM nifedipine and 2 μM nifedipine with 2 mM heptanol on contractions elicited by addition of 20 μM NA to the organ bath for 2 min.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction observed with heptanol alone was not significantly different than that induced by heptanol in tissues preincubated with nifedipine (P>0.01), indicating involvement of similar mechanisms in the presence or absence of nifedipine. Heptanol has also been suggested to exert other non-junctional actions in various tissues (activation of KCa channels, reduction of [Ca 2+ ]i (Matchkov et al, 2004); voltage-dependent Na + current suppression (Nelson and Makielski, 1991); decreased voltage-dependent K + and Ca 2+ currents (Perez-Armendariz et al, 1991)). However, in a recent detailed characterization of its effects on vascular smooth muscle cells (Matchkov et al, 2004), it was shown that heptanol, over the range of concentrations used in our study (0.5-2.0 mM), potently increased the input resistance of the cells and desynchronized their [Ca 2+ ]i oscillations, indicating that it powerfully uncoupled the cells.…”
Section: Role Of Cell-to-cell Coupling In Na-induced Contractionmentioning
confidence: 99%
See 2 more Smart Citations